Software Clone Detection and Refactoring. (19th March 2013) - Arcelli Fontana, Francesca; Zanoni, Marco; Ranchetti, Andrea; Ranchetti, Davide
Abstract : Several studies have been proposed in the literature on software clones from different points of view and covering many correlated features and areas, which are particularly relevant to software maintenance and evolution. In this paper, we describe our experience on clone detection through three different tools and investigate the impact of clone refactoring on different software quality metrics.